2013
DOI: 10.1111/acer.12149
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Control of Alcohol Use and Severity of Alcohol Dependence in Non‐Treatment‐Seeking Heavy Drinkers Are Related to Lower Glutamate in Frontal White Matter

Abstract: In contrast to the rather unspecific rise in choline-containing compounds, low Glu in frontal WM may be specific for the shift from nondependent heavy drinking to dependence and does not reflect a simple effect of the amount of alcohol consumption alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 46 publications
2
31
0
Order By: Relevance
“…Moreover, FA, NAA, and tCho were each significantly correlated with FH density (number of parents and grandparents with substance use disorders), and these relationships were not affected by removing participants who had psychiatric conditions or had tried alcohol or other drugs. Our results parallel findings of reduced NAA and elevated tCho in frontal white matter of individuals with alcohol and other drug use disorders [Ende et al, ; Licata and Renshaw, ] and suggest this altered pattern may be present prior to the initiation of alcohol or other drug use in at risk individuals.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, FA, NAA, and tCho were each significantly correlated with FH density (number of parents and grandparents with substance use disorders), and these relationships were not affected by removing participants who had psychiatric conditions or had tried alcohol or other drugs. Our results parallel findings of reduced NAA and elevated tCho in frontal white matter of individuals with alcohol and other drug use disorders [Ende et al, ; Licata and Renshaw, ] and suggest this altered pattern may be present prior to the initiation of alcohol or other drug use in at risk individuals.…”
Section: Discussionsupporting
confidence: 89%
“…These lower occipital or ACC (into adjacent white matter) glutamate levels were correlated with greater drinking severity [e.g., more alcohol-related consequences (Thoma et al, 2011), loss of control over drinking (Ende et al, 2013)] or poorer neuropsychological functioning [e.g., more impaired visual-motor or attentional functioning (Bagga et al, 2014; Pennington et al, 2014)]. In contrast, other studies reported no differences between alcohol-addicted individuals and controls in glutamate or Glx in the cerebellar vermis (Seitz et al, 1999), dorsolateral PFC (DLPFC) (Nery et al, 2010), or dACC (Yeo et al, 2013).…”
Section: Glutamatergic Alterations In Drug Addiction (Table 1)mentioning
confidence: 99%
“…1 H‐MRS investigations of anterior cingulate glutamate in AD have produced seemingly conflicting results, with reports of increased (Lee et al., ), decreased (Thoma et al., ), and equivalent glutamate levels among AD relative to non‐AD individuals (Bauer et al., ; Yeo et al., ). However, when independent cross‐sectional 1 H‐MRS investigations of glutamate in AD are sorted by time since participants' last drink, the literature as a whole supports that brain glutamate levels in individuals with AD are abnormally low during active drinking (e.g., <24 hours from last alcohol consumption; Ende et al., ), abnormally high during acute withdrawal (e.g., 48 to 72 hours from last alcohol consumption; Hermann et al., ), and abnormally low once again 1 week from last alcohol consumption (Mon et al., ). Additional research suggests that anterior cingulate cortex (ACC) glutamate levels may normalize approximately 2 to 5 weeks from last alcohol consumption (Hermann et al., ; Mon et al., ).…”
mentioning
confidence: 99%